Padrão de distribuição da micota liquenizada em unidades de paisagem do semiárido sergipano - Pereira, Thamires Almeida (2022)
Lichens are small structures formed by the association of two or more organisms, a fungus and an algae or cyanobacteria, some recent studies show the presence of yeast-like basidiomycetes. They are pioneer organisms, responsible for inhabiting inhospitable environments and frequently used as bioindicators, but studies correlating lichen distribution with geoenvironmental characteristics have not been carried out, which is a pioneering work. Thus, the objective of the study is to develop a georeferenced database with the geoenvironmental characteristics of the landscapes where lichens occur, in the Caatinga Sergipana, with the following hypotheses being proposed: the locations have similar physical-geographical characteristics (H1); lichens from the semiarid region of Sergipe have a similar distribution pattern (H2). The survey of lichenized mycota was carried out in the collection of the Herbarium ISE - UFS, six locations were contacted: Poço Redondo (PR), Monte Alegre de Sergipe (MA), Porto da Folha (PF), Nossa Senhora da Glória (NSG), Pedra Mole (PM) and Poço Verde (PV). To verify the geoenvironmental data, cartographic modeling was used to describe the typologies of the geosystems, using the methodology adapted from Cavalcanti (2013, 2018). 2713 records of lichens were observed in the semiarid region of Sergipe, distributed in 255 species, 51 genera and 21 families. In PR obtained 27 genera and 61 species, PV 43 genera and 175 species, MA 30 genera and 75 species, NSG obtained 16 genera and 28 species, PM 14 genera and 28 species, PF 15 genera and 22 species. The most representative families were Arthoniaceae, Graphidaceae, Lecanoraceae, Pyrenulaceae and Trypetheliaceae. Of the geological formations detected, the mucururé group was the most predominant, occurring in 50% of the regions studied. The rock classes identified were metamorphic and igneous, the metamorphic stood out, being present in 83.3% of the landscapes. In 67% of the areas the wind direction was to the Northeast – NE, and in 33% Southeast –SE, the temperature of the landscapes varied between 22.9ºC and 25.3ºC and the precipitation varied from 523 mm to 844 mm. 67% of the landscapes have a medium clayey texture, and 33% have sandy textured soils. The use and land cover of the regions that stood out was the savanna formation (forest), the MSAVI had a variation between 0.36 and 0.45, classified as moderate vegetation. Thus, a possible spatial correlation between the attributes is observed, but in general there is no pattern of distribution of lichenic biota as a function of the attributes studied.